Impact of Muscle Relaxation on Blood Pressure in Primary Hypertension Patients Sudiang Raya Makassar 2024 - Herdiansyah, Muh.; Arifin, Arina Fathiyyah; Muchsin, Achmad Harun; Wahyu, Sri; Arfah, Arni Isnaini (Jurnal Biologi Tropis, 2024)
Hypertension is a serious disease that causes serious complications such as stroke, local myocardial necrosis, cardiovascular disorders, and kidney failure. Hypertension is often nicknamed the "Silent Killer" because it has no side effects. Information from the World Wellbeing Association (WHO) in 2015 shows that this figure will increase to 1.5 billion cases in 2025. The 2018 Fundamental Welfare Exploration (Riskesdas) in Indonesia revealed that the prevalence of hypertension in the population aged over 18 years was 658,201 cases. Moderate muscle relaxation exercises are a non-pharmacological measure that can help lower blood pressure. It is hoped that this examination will determine the relationship between muscle relaxation and reduced blood pressure in essential hypertension patients at the Sudiang Raya Makassar Community Welfare Center. The technique used is One Gathering Pretest-Posttest Plan. Information is dissected using the T test Suitable for evaluating differences in blood pressure during testing. The results of the review showed a significant reduction in systolic and diastolic blood pressure after moderate muscle release treatment, with a p value of 0.000 (p<0.05). Systolic and diastolic blood pressure were reduced by 9.31 mmHg and 4.76 mmHg respectively. There is an effect of mild muscle relaxation treatment on reducing blood pressure in essential hypertension patients at the Sudiang Raya Makassar Community Welfare Center.